Acupuncture Ameliorates Alzheimer’s-Like Cognitive Impairment and Pathological Changes via Regulating the Intestinal Fungal Community in APP/PS1 Mice - Hao X; Ding N; Zhang Y; Wu M; Tao Y; Li Z (Neuropsychiatric Disease and Treatment)
Xin Hao,1,* Ning Ding,2,* Yue Zhang,3 Meng Wu,1 Yilin Tao,1 Zhigang Li1 1School of Acupuncture, Moxibustion and Tuina, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of China; 2Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People’s Republic of China; 3Guangzhou University of Chinese Medicine Meizhou Hospital (Meizhou Hospital of Chinese Medicine), Guangzhou, 514000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ning Ding, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People’s Republic of China, Email beijingdingning@163.com Zhigang Li, School of Acupuncture, Moxibustion and Tuina, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of China, Email lizhigang620@126.comBackground: The disorder of the intestinal fungal community is closely associated with Alzheimer’s disease (AD). Gut fungal dysbiosis exacerbates β-amyloid (Aβ) plaque burden through the brain-gut axis, thereby promoting the progression of AD. Previous research has demonstrated that acupuncture can ameliorate AD symptoms by modulating the gut bacterial community. However, the potential regulatory effects of acupuncture on the fungal microbiota have been largely overlooked.Methods: APP/PS1 mice were used as AD animal model and randomly divided into the AD model (AD) group, the acupuncture (Ac) group, and the probiotics (Pr) group. Mice in the Ac group received acupuncture treatment. In the Pr group, mice were treated with probiotics. Morris water maze, ITS sequencing, immunofluorescence (IF) staining, enzyme-linked immunosorbent assay (ELISA), Hematoxylin and eosin analysis, and Nissl staining were employed to validate our hypothesis.Results: Acupuncture and probiotics significantly improved the behavioral performance of APP/PS1 mice, reduced the level of Aβ in the brain, and alleviated neuronal damage. Moreover, acupuncture improved the Sobs, Chao and Ace indices, decreased the abundance of Ascomycota, Aspergilaceae, Trichocomaceae, Candida, and unclassified-penicillium, while simultaneously increasing the abundance of Basidiomycota, which differed from the fungal regulation observed with probiotics.Conclusion: Acupuncture may improve the cognitive impairment of APP/PS1 mice, reduce Aβ plaque burden in the brain, protect neurons, and mitigate intestinal fungi dysbiosis. The beneficial effects of acupuncture on Aβ deposition and cognitive function in APP/PS1 mice may be achieved by regulating the intestinal fungal community.Keywords: Alzheimer’s disease, acupuncture, intestinal fungal community, β-amyloid, probiotics